Supervision in the Management of State-Owned Non-Movable Assets (Land) at the Class II Type A Navigation District Office, Benoa - Dalmonce Dalmonce; Erikson Sihotang; I Made Mulyawan Subawa (International Journal Labs, 2025)
Supervision in the management of immovable State Property (BMN), especially land, is one of the crucial aspects to ensure accountability and optimization of state assets. This study aims to analyze the effectiveness of supervision in soil management at the Benoa Class II Type A Navigation District Office. A qualitative descriptive approach is used with data collection techniques through interviews, field observations, and document studies. The results of the study show that supervision has been carried out in accordance with applicable regulations, but there are still several obstacles, such as limited human resources, lack of asset data updates, and less optimal coordination between related agencies. In addition, it was found that there was a risk of potential land disputes due to the lack of clear ownership limits. To increase the effectiveness of supervision, it is recommended that data be updated regularly, human resource capacity building through training, and strengthening coordination with related parties. The implementation of information technology is also expected to support transparency and accuracy in land management as BMN.